TYPES OF COMMERCIAL AND SERVICE LOGISTICS AND THEIR AREAS OF ACTIVITY - Xasanov Ibrohim Abdulxamid o’g’li,; Ahmedov R.M., (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Commercial and service logistics are essential for the efficient movement of goods, services, and information in modern economies. This article examines the main types of commercial and service logistics and their areas of activity. It highlights the importance of logistics in improving operational efficiency, reducing costs, and ensuring high-quality service across various sectors.